Hero or villain? Moral ambiguity and narrative structure under the Comics Code in 1950s Superman stories. Issue 2 (1st November 2019) - Traver, John C.
AbstractThis article explores the decades-long influence of the Comics Code on American comic books' storytelling form by identifying the interpretive processes underlying the Code's application and adapting the Code as a theoretical model for approaching the narrative structure and implied ethical stance within 1950s Superman comics. Instead of treating the Comics Code as a series of regulations seemingly interpreted arbitrarily, this article explores how interpretive issues were framed by figures such as Charles Murphy, Leonard Darvin and John Goldwater to identify 'the spirit and intent of the Code' and resolve challenges such as distinguishing between the 'spirit' and 'letter' of the Code, identifying interpretive authority outside the Code, weighing past interpretive precedent and locating authorial 'intent'. Ambiguities and aporia within the Code's language demanded that administrators reconstruct the Code's possible meanings and conceptualize 'justice' by distinguishing between the Code's general preferences and actual prohibitions, resolving terminological nuance and prioritizing conflicting stipulations. Administrators' efforts to balance competing stipulations regarding characters' physical unattractiveness, criminality, justice and institutional authority shaped comics' storytelling form and perpetuated ambiguities that comic creators could ‐ intentionally or unintentionally ‐ exploit. Where Silver Age DC Comics have often been viewed as sacrificing psychological complexity to plotting and social conformity, this article argues that the plotting intricacy in several 1950s Comics-Code era Superman comics in fact enabled writers to present a more complex rendering of moral issues. Where the Comics Code explicitly forbade that 'crimes' be 'presented in such a way as to create sympathy for the criminal', the Comics Code's own textually unstable meaning ‐ coupled with the narrative complexity of the stories' plotting, shifting points of view and situational and dramatic irony ‐ enabled 1950s Superman writers to create sympathy for a supposed 'criminal', depict the frequent inaccuracy of assumed knowledge and introduce moral ambiguity, all while arguably 'following' the Code.